2009
DOI: 10.2189/asqu.2009.54.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Tilting at Windmills? The Environmental Movement and the Emergence of the U.S. Wind Energy Sector

Abstract: Through a study of the emergent U.S. wind energy sector, 1978–1992, this paper examines how large-scale social movements external to an industry can influence the creation of new market opportunities and hence encourage entrepreneurship. We theorize that through the construction and propagation of cognitive frameworks, norms, values, and regulatory structures, and by offering a preexisting social structure, social movement organizations influence whether entrepreneurs attempt to start ventures in emerging sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
417
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(437 citation statements)
references
References 83 publications
11
417
0
1
Order By: Relevance
“…Applied to entrepreneurship, this fits with the argument that the creation of a supportive institutional environment is required for ventures that pursue novel business models (Aldrich & Fiol, 1994;Navis & Glynn, 2010). It also mirrors a consistent finding among microfinance (Ledgerwood, 2011), recycling , greenbuilding (York & Lennox, 2014), and wind energy (Sine & Lee, 2009) studies where early entrepreneurs engaged in efforts to not only develop, but also garner social support for, novel business models. We argue that the roots of such efforts may be found within the tensions experienced by balanced entrepreneurs, who have salient role identities that carry conflicting behavioral demands.…”
Section: Page 29 Of 55supporting
confidence: 65%
“…Applied to entrepreneurship, this fits with the argument that the creation of a supportive institutional environment is required for ventures that pursue novel business models (Aldrich & Fiol, 1994;Navis & Glynn, 2010). It also mirrors a consistent finding among microfinance (Ledgerwood, 2011), recycling , greenbuilding (York & Lennox, 2014), and wind energy (Sine & Lee, 2009) studies where early entrepreneurs engaged in efforts to not only develop, but also garner social support for, novel business models. We argue that the roots of such efforts may be found within the tensions experienced by balanced entrepreneurs, who have salient role identities that carry conflicting behavioral demands.…”
Section: Page 29 Of 55supporting
confidence: 65%
“…For example Russo showed that industry associations and the number of existing renewable projects helped the development of new projects. Sine and Lee (2009) found that environmental groups had a larger impact on entrepreneurial activity in the wind energy sector than the avail ability of natural resources. Similarly, Vachon and Menz (2006) and Lyon and Yin (2010) found that political and social interests were positively and significantly related to the developments of renewable energy projects.…”
Section: The Context Of Renewable Policiesmentioning
confidence: 99%
“…Indeed, scholars have argued that natural capital must be com plemented by social and political capital to drive the adoption of renewable policies and the development of new technologies and investments in renewable resources (Lyon and Yin, 2010;Russo, 2003;Sine and Lee, 2009;Vachon and Menz, 2006). For example Russo showed that industry associations and the number of existing renewable projects helped the development of new projects.…”
Section: The Context Of Renewable Policiesmentioning
confidence: 99%
“…Indeed, even the simple fact that species conservation banks are concentrated in California-a state home to a storied and influential environmental movement (Gottlieb 2005;Sine and Lee 2009) and with environmental regulations that may look more European than American (Vogel 2012)-suggests that the rise of these institutions is coupled to far more than just profit-seeking or even green-minded entrepreneurialism. Stringent environmental rules, environmental groups, and California's general environmental exceptionalism are instead signaled by the data, and at the very least must intersect with the environmental-economic explanations highlighted by existing social scientific accounts.…”
Section: [Figure 4 About Here]mentioning
confidence: 99%